STRATEGI PENGEMBANGAN UMKM MENDONG DI KECAMATAN WAJAK, KABUPATEN MALANG - Novitawati, Retno Ayu Dewi; Mutiara, Farah; Kholil, A. Yusuf (Universitas Tribhuwana Tunggadewi, 2023)
The development of the Mendong Craft Agro-Industry Center in Malang Regency has experienced several obstacles, including inadequate infrastructure conditions, low training capacity, the dominance of middlemen, non-functioning institutions, and low specialization and competitiveness of the center. This research aimed to identify characteristics and factors that influence development using multivariate factor analysis, develop concepts and strategies using SWOT and IFAS-EFAS analysis, and develop development directions (physical-spatial) for the Mendong Crafts agro-industry center, Malang Regency. The Mendong Crafts agro-industry center in Malang Regency has the characteristics of local economic development except for organizational structure, RD, legal entities, and collaboration with capital institutions. The characteristics of clusters are spatial proximity, interaction, combination of competencies, and identity.